2012
DOI: 10.1039/c2nr31530k
|View full text |Cite
|
Sign up to set email alerts
|

Local boron environment in B-doped nanocrystalline diamond films

Abstract: Thin films of heavily B-doped nanocrystalline diamond (B:NCD) have been investigated by a combination of high resolution annular dark field scanning transmission electron microscopy and spatially resolved electron energy-loss spectroscopy performed on a state-of-the-art aberration corrected instrument to determine the B concentration, distribution and the local B environment. Concentrations of $1 to 3 at.% of boron are found to be embedded within individual grains. Even though most NCD grains are surrounded by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…First, recent density functional theory (DFT) ELNES calculations for single substitutional B in diamond properly reproduced the three r* peaks as well as a small pre-peak 8.7 eV before the first r* peak arising from states in the band-gap. 5 This energy position is in excellent agreement with our experimental data for pre-peak 1. Second, literature data from B-doped Fe-Cr oxide reveal a strong p* signature for B at 193.5, which is again in good agreement with our value of 193.8 eV.…”
Section: Direct Visualization Of Boron Dopant Distribution and Coordisupporting
confidence: 89%
See 1 more Smart Citation
“…First, recent density functional theory (DFT) ELNES calculations for single substitutional B in diamond properly reproduced the three r* peaks as well as a small pre-peak 8.7 eV before the first r* peak arising from states in the band-gap. 5 This energy position is in excellent agreement with our experimental data for pre-peak 1. Second, literature data from B-doped Fe-Cr oxide reveal a strong p* signature for B at 193.5, which is again in good agreement with our value of 193.8 eV.…”
Section: Direct Visualization Of Boron Dopant Distribution and Coordisupporting
confidence: 89%
“…Our own recent work showed that even though B was present in the amorphous grain boundaries in CVD B:NCD, no clear enrichment of the boron at grain boundaries was apparent. 5 Inside individual diamond grains, the density of extended planar lattice defects has also been shown to be considerably higher in B:NCD diamond films from CVD, an indication that B could well be enriched at planar defects and other defect centers. 6 However, the atomic scale of planar defects, the relatively low B concentration, and problems of specimen preparation for NCD films have strongly hindered the acquisition of detailed experimental data until now.…”
Section: Direct Visualization Of Boron Dopant Distribution and Coordimentioning
confidence: 96%
“…For example, the tetrahedral configuration can be deduced from the nitrogen K edge structure [51,60]. Recent work shows this technique permits to confirm the tetrahedral insertion of boron atoms in diamond leading to p-doping [61,62]. EELS combined with scanning TEM (STEM) can even provide mapping or profiles of impurities with an atomic resolution [63][64][65].…”
Section: Diamond Corementioning
confidence: 97%
“…Moreover, the extinction coefficient increased with increasing a wavelength in the wavelength region above 350 nm. This can be explained by a higher sp 2 bond content and intensive boron incorporation between the grains [61] (see Table 3. ).…”
Section: /Spmentioning
confidence: 99%